Effect Student and Teacher Response to the use of Interactive Multimedia in the Learning Process - Silfia Andini; Aulia Hadi (Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to analyze how the response of class XI students and the response of the teacher at SMK PERBANKAN Padang to the use of Interactive Multimedia in the learning process. There were 150 students and 8 teachers at the school who were the research samples. In this study, there are two problems investigated, namely how students respond to the use of Interactive Multimedia in the learning process of learning and how the teacher responds to the use of Interactive Multimedia in the learning process of learning. The data obtained in this study were in the form of student response questionnaire data and teacher response questionnaire data. The data were analyzed using descriptive analytical methods to obtain answers to the problems in the study. Based on the results of the study, it was found that 88% of students responded positively to the use of interactive multimedia in the learning process of mathematics. And as many as 75% of teachers responded positively to the use of interactive multimedia in the learning process because learning activities carried out using interactive multimedia were more active and felt fun for students and teachers.